ENDOVASCULAR AV FISTULA SALVAGE IN PEDIATRIC PATIENTS: INITIAL EXPERIENCE AT IKDRC ITS (Asian Journal of Medical Research and Health Sciences, 2026)
Early transplantation is the preferred treatment for children with end stage renal disease (ESRD); 30% of these patients still need hemodialysis (HD). In cases of arteriovenous fistula (AVF) failure, endovascular AVF salvage procedures hold promise for AVF salvage. These procedures have an established role in AVF failure in adult patients. In this study, we have performed similar endovascular AVF salvage procedures in pediatric patients and follow them for 1-year patency. Results showed, primary patency rate at 1-year post AVF salvage was 82%. We concluded that in pediatric patients, endovascular AVF salvage procedures help in case of AVF failure. It is helpful as preservation of a vascular access site and/or a bridge procedure until renal transplantation.